How and why patients made Long Covid - Callard, Felicity; Perego, Elisa (Social science & medicine (1982), 2021)
Patients collectively made Long Covid – and cognate term ‘Long-haul Covid’ – in the first months of the pandemic. Patients, many with initially ‘mild’ illness, used various kinds of evidence and advocacy to demonstrate a longer, more complex course of illness than laid out in initial reports from Wuhan. Long Covid has a strong claim to be the first illness created through patients finding one another on Twitter: it moved from patients, through various media, to formal clinical and policy channels in just a few months. This initial mapping of Long Covid – by two patients with this illness – focuses on actors in the UK and USA and demonstrates how patients marshalled epistemic authority. Patient knowledge needs to be incorporated into how COVID-19 is conceptualised, researched, and treated. •Patients made visible the persistence and heterogeneity of COVID-19 symptoms.•Patients experiencing long-term symptoms (‘long-haulers’) made Long Covid.•Long Covid challenges early clinical and governmental assumptions about Covid.•Knowledge travelled from patients through media to formal health and policy channels.•Patient expertise and knowledge should be incorporated in the pandemic evidence base.